Influence of natural and anthropogenic disturbances on foraminifera and free-living nematodes in four lagoons of the Po delta system. (1st May 2019) - Franzo, A.; Asioli, A.; Roscioli, C.; Patrolecco, L.; Bazzaro, M.; Del Negro, P.; Cibic, T.
Abstract: The natural high productivity of river lagoons has always attracted human activities of high economic value such as aquaculture. Notwithstanding, these environments are also prone to contamination, excessive organic enrichment and hypoxic/anoxic events due to the synergy between natural (e.g. fluctuations of oxygen, temperature and salinity) and anthropogenic factors (e.g. accumulation of pollutants carried by the river). In order to minimize any economic loss and potential risk for human health, river lagoons are kept under surveillance by means of monitoring campaigns that rarely include foraminifera and nematoda despite their suitability as ecological indicators. In May 2016, these two assemblages were investigated within the framework of the project RITMARE in four lagoons of the Po Delta system (Adriatic Sea) in terms of taxonomic composition, biodiversity and biological traits. Dominated by a few tolerant taxa ( Ammonia tepida and Haynesina germanica for foraminifera; Daptonema, Tershellingia and Sabatieria for nematoda), both assemblages seemed adapted to conditions of environmental instability mainly ascribable to natural disturbance factors rather than to anthropogenic contamination, as indicated by the DISTLM outputs. Furthermore, the stochastic occurrence of abnormal tests and the presence of numerous organisms in subsurface sediment levels confirmed a limited effect of synthetic organic compounds (e.g. aromatic hydrocarbons and polybrominated diphenyl ethers) and trace metals on foraminifera. Focusing on nematoda, the assemblage seemed more sensitive in reflecting the peculiar environmental conditions of each lagoon and the degree of confinement, as indicated by the significant intra- and inter-lagoon variability detected for the majority of the tested metrics. In particular the significantly less biodiverse assemblage dominated by r-strategist (i.e. pioneer) organisms at the inner and middle stations of Scardovari may represent the nematoda response to recent hypoxic/anoxic conditions that often occur in the inner areas of this lagoon because of its low water renewal. Both assemblages showed to be suitable for the implementation of monitoring programs; from the study of foraminifera, a relatively low chemical contamination was inferred while, from that of nematodes, recent events of oxygen deficiency were detectable. Highlights: Foraminifera and nematoda were synoptically studied in 4 lagoons of the Po Delta. Foraminifera were scarcely impacted by organic contaminants and trace metals. Responses to hypoxic events were detected for nematoda but not for foraminifera. Disturbance factors were natural and mainly ascribable to lagoon hydrodynamics. The study of both assemblages may implement monitoring actions in riverine lagoons.